THE HISTORY OF ASHURALI ZOHIRIY'S PUBLISHING AND JOURNALISTIC ACTIVITY (Conferencea, 2025)
Ashurali Zahiri, one of the representatives of the literary milieu of the 20th century Kakand, joined the Jadidist movement in 1910. He began to participate in the cultural reforms of the Jadids. He took part in the creation of the society "Taraqqiparvarlar" of Jadids, which arose in the Fergana Valley. This society focused on thinking about and supporting the education of young people for the future of Turkestan. Together with Ferghana Jadid intellectuals, he opened and taught new schools of method. He carried out his activities in the direction of one goal, in connection with the Turkestan moderns, around the important issues of the reformist movements.